IJIMAI Editor's Note - Vol. 4 Issue 1 - Bahaj, Mohamed (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2021)
The research works presented in this issue are based on various topics of interest, among which are included: Pattern Recognition, Multimedia Information Retrieval, Knowledge extraction and knowledge mining, Data mining, Intelligent Systems & Artificial Intelligence, Wireless Technology, Network Telecommunication, Security & Network Management, Advanced Network Technologies.
Keywords: Editors Note; IJIMAI